Signifying the Crucial Role of Performance Measurement in Istibdal Waqf Projects in Malaysia - Nor Amni Bazilah Mohd Zain; Fuadah Johari (Universiti Sains Islam Malaysia, 2024)
The Journal of Muamalat and Islamic Finance Research,Volume 21 Issue 2 Page (59-76)